SPA70 is a potent antagonist of human pregnane X receptor - Wenwei Lin; Yue-Ming Wang; Sergio C. Chai; Lili Lv; Jie Zheng; Jing Wu; Qijun Zhang; Yong-Dong Wang; Patrick R. Griffin; Taosheng Chen (Nature Communications, 2017)
The xenobiotic-activated human pregnane X receptor (hPXR) regulates drug metabolism. Here the authors develop hPXR modulators, which are of potential therapeutic interest and functionally and structurally characterize the antagonist SPA70 and the structurally related agonist SJB7.